EKSPERIMENTASI MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER DAN THINK-TALK-WRITE DENGAN PENDEKATAN SAINTIFIK PADA MATERI SISTEM PERSAMAAN DAN PERTIDAKSAMAAN DITINJAU DARI SIKAP PERCAYA DIRI SISWA KELAS X PEMINATAN IPA SMA NEGERI DI KOTA SURAKARTA - Putri, Diah Purwaning; Budiyono, Budiyono; Sari Saputro, Dewi Retno (Jurnal Pembelajaran Matematika, 2016)
Abstract : The purpose of Â this study was to determine the effect of the learning models on the learning achievement in Mathematics seen from the self confidence attitude of the students. The learning models compared were the cooperative learning model of the Numbered Head Together (NHT) type using scientific approach, Think Talk Write (TTW) type using scientific approach, and classical model using scientific approach.This study was a quasi-experimental with a 3x3 factorial design. Instruments used for data collection were mathematics learning achievement tests and a questionnaire of student self confidence attitude. The proposed hypothesis of the research were analyzed by using the two way analysis of variance with unbalanced cells. Based on the hypothesis testing it can be concluded as follows.Â  (1) The mathematics learning achievement of student with NHT learning model using scientific approach are as high as that of the students with TTW learning model using scientific approach, the learning achievement of students with NHT learning model using scientific approach are as high as that of the students with classical learning model using scientific approach, and the learning achievement of students with TTW learning model using scientific approach is better than that ofÂ  students with classical learning model using scientific approach, (2) high self confidence studentsâ learning achievement is as high as medium self confidence studentsâ, the high self confidence studentsâ learning achievement is better than the low self confidence studentsâ, and the medium self confidence studentsâ learning achievement is better than the low self confidence studentsâ, (3) Seen from self confidence attitude, the mathematics learning achievement of student with NHT learning model using scientific approach are as high as that of the students with TTW learning model using scientific approach, the learning achievement of student with NHT learning model using scientific approach are as high as that of the students with classical learning model using scientific approach, and the learning achievement of student with TTW learning model using scientific approach is better thanÂ  students with classical learning model using scientific approach), (4) seen from the learning models, high self confidence studentsâ learning achievement is as high as medium self confidence studentsâ, the high self confidence studentsâ learning achievement is better than the low self confidence studentsâ, and the medium self confidence studentsâ learning achievement is better than the low self confidence studentsâKeywords: Number Head Together, Think Talk Write, Classical, Self Confidence Attitude